2022
DOI: 10.3389/fmicb.2022.1013258
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cellulase and lactic acid bacteria on the fermentation quality, carbohydrate conversion, and microbial community of ensiling oat with different moisture contents

Abstract: Oat (Avena sativa L.) is one of the most widely cultivated crops used as forage. The aim of this study was to evaluate the effects of cellulase and Lactobacillus plantarum interactions with different moisture contents on oat ensiling. Oats with three moisture contents were treated with nothing (C), cellulase (CE), lactic acid bacteria (LP), or CE+LP and ensiled for 30 and 60 days. Compared with the control, LP and CE treatments increased crude protein and lactic acid concentrations and reduced the pH and ammon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 51 publications
10
10
0
Order By: Relevance
“…HMEC from each treatment in this experiment were individually aggregated within a narrow range, indicating good reproducibility of the samples and significant separation and differences in the distribution and composition of the microbial community across treatments. This result suggested that different total classes of additives as well as different moisture could significantly affect the microbial composition of HMEC, which is in agreement with the results of Xu et al (2022) about the effect of moisture and additives on the microbial composition of the community in silage.…”
Section: Discussionsupporting
confidence: 90%
“…HMEC from each treatment in this experiment were individually aggregated within a narrow range, indicating good reproducibility of the samples and significant separation and differences in the distribution and composition of the microbial community across treatments. This result suggested that different total classes of additives as well as different moisture could significantly affect the microbial composition of HMEC, which is in agreement with the results of Xu et al (2022) about the effect of moisture and additives on the microbial composition of the community in silage.…”
Section: Discussionsupporting
confidence: 90%
“…This indicated that the fermentation of the mixed silage of king grass and rice straw was dominated by homofermentation. Consistently, Liu et al showed that the abundance of Lactiplantibacillus was positively correlated with WSC content [ 51 ], and Lactiplantibacillus had a positive effect on nutrient preservation [ 52 ].…”
Section: Discussionmentioning
confidence: 93%
“…The relative abundance of Proteobacteria was lower in the PAA 2000 and CTC 500 groups than in the control group. Proteobacteria play a pivotal role in fermentation [56]. Proteobacteria consist mostly of pathogenic bacteria [57].…”
Section: Discussionmentioning
confidence: 99%